Aicardi-Goutières syndrome: A cause of CSF chronic hyperlymphocytosis - Akopova-Larbi, Rosana; Turki, Ilhem Ben Youssef; Kraoua, Ichraf; Gouider-Khouja, Neziha (Journal of Pediatric Neurology, 2010)
Aicardi-Goutières syndrome (AGS) is a rare infantile encephalopathy characterized by basal ganglia calcifications, leukodystrophy, chronic pleocytosis and elevated levels of interferon-alpha in cerebrospinal fluid. AGS is a clinically and genetically heterogeneous syndrome. We report an early onset case of AGS. Consanguinity, similar picture in the family and course suggested a familial metabolic encephalopathy. Extended basal ganglia calcifications and leukodystrophic changes on cerebral imaging, cerebrospinal fluid lymphocytosis and high interferon-alpha level allowed to diagnose AGS. We reviewed the literature and discussed the pathophysiology, differential diagnosis and treatment of this disorder.
Keywords: Infantile encephalopathy; microcephaly; basal ganglia calcifications; leukodystrophy; CSF lymphocytosis